Chemoradiotherapy plus induction or consolidation chemotherapy as total neoadjuvant therapy for locally advanced rectal cancer: Pooled analysis of the CAO/ARO/AIO-12 and the OPRA randomized phase 2 trials - Fokas, Emmanouil; Williams, Hannah; Diefenhardt, Markus; Lin, Sabrina; Qin, Li Xuan; Piso, Pompiliu; Dapper, Hendrik; Germer, Christoph Thomas; Grützmann, Robert; Tim Friede, J.; Joshua Smith, J.; Saltz, Leonard B.; et al. (European Journal of Cancer, 2024)
Background: Total neoadjuvant therapy (TNT) has been used for patients with locally advanced rectal cancer. The optimal sequence of chemoradiotherapy (CRT) and chemotherapy (CT) is a matter of debate. Methods: We performed a pooled analysis of the CAO/ARO/AIO-12 and OPRA multicenter, randomized phase 2 trials to identify patient subsets that could benefit from one TNT sequence over the other regarding disease-free survival (DFS). Patients with stage II/III rectal cancer were randomized to CRT (50.4–54 Gy) with either induction (INCT-CRT) or consolidation CT (CRT-CNCT) with fluorouracil, leucovorin, oxaliplatin (CAO/ARO/AIO-12 and OPRA) or capecitabine and oxaliplatin (OPRA) followed by mandatory total mesorectal excision (TME) (CAO/ARO/AIO-12) or selective watch-and-wait surveillance (OPRA). 311 and 324 patients were recruited from June 15, 2015 to January 31, 2018; and from April 12, 2014 to March 30, 2020 in the two trials, respectively. Pretreatment clinical and tumor characteristics included were age, sex, ECOG, cT-category, cN-category, clinical UICC stage, location from anal verge, and tumor grade. Findings: In total, 628 eligible patients were included in the pooled analysis (CAO/ARO/AIO-12, n = 304; OPRA, n = 324). Of those, 313 were randomly assigned to the INCT-CRT group, and 315 to the CRT-CNCT group. Median follow-up was 43 months (IQR, 35–49) months in the CAO/ARO/AIO-12 trial and 61,2 months (IQR, 42–68,4) in the OPRA trial. Pooled analysis of baseline clinical and tumor characteristics did not identify any subgroups of patients that would benefit by the one TNT sequence over the other with regard to DFS. Interpretation: To our knowledge, this is the first pooled analysis of two randomized trials after direct head-to-head comparison of both TNT sequences. Both trials reported higher rates of complete response with CRT-CNCT, and this should be considered the preferred TNT sequence if organ preservation is a priority.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Oncological guidelines; Pooled analysis; Randomized trials; Rectal cancer; Sequence; Total neoadjuvant treatment